Ibuprofen increases soft tissue infections in children (2008)
Because ibuprofen is more effective as monotherapy than paracetamol in controlling fever in children Hay and colleagues conclude that ibuprofen should be administered first to feverish children in discomfort.1 Paracetamol should be added after 24 hours if recovery is no